2013
DOI: 10.1093/jrr/rrt028
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy for primary vaginal carcinoma

Abstract: Brachytherapy plays a significant role in the management of cervical cancer, but the clinical significance of brachytherapy in the management of vaginal cancer remains to be defined. Thus, a single institutional experience in the treatment of primary invasive vaginal carcinoma was reviewed to define the role of brachytherapy. We retrospectively reviewed the charts of 36 patients with primary vaginal carcinoma who received definitive radiotherapy between 1992 and 2010. The treatment modalities included high-dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 18 publications
2
24
1
1
Order By: Relevance
“…2Y4 Some retrospective studies have shown that non-SCC is a strongly negative factor for local control. 13,20 However, in our study, vaginal recurrence was observed in only 2 patients. Thus, surgical resection for non-SCC can be a treatment option.…”
Section: Discussioncontrasting
confidence: 70%
“…2Y4 Some retrospective studies have shown that non-SCC is a strongly negative factor for local control. 13,20 However, in our study, vaginal recurrence was observed in only 2 patients. Thus, surgical resection for non-SCC can be a treatment option.…”
Section: Discussioncontrasting
confidence: 70%
“…In the study by Frank et al , which included only patients with AC VC, the authors recorded a higher incidence of metastases and poor LC and OS compared with patients with SCC VC treated in the same period . Murakami et al reported poor LC for patients with a non‐SCC histologic subtype of VC ( p < .001) .…”
Section: Resultsmentioning
confidence: 99%
“…In fact, only five of the ten studies in which some patients received C‐CT reported the specific results in this subgroup of patients or presented a comparison with RT alone. In four studies, C‐CT was based on weekly cisplatin in most patients , and in another study the chemotherapy drugs were not specified . Only one study reported toxicity in patients undergoing C‐CT (grade ≥3 acute, 20%; late, 20%) .…”
Section: Resultsmentioning
confidence: 99%
“…Jang et al [18] had suggested that definitive radiotherapy is an effective treatment modality, and local control translated to diseasefree and overall survival. Murakami et al [20] concluded that combination of EBRT and HDR brachytherapy provides a good local control. Customized vaginal applicators with central and peripheral channels for differential loading and optimized dose delivery, using Iridium-192 alone, or Iridium-192 and Cesium-132 in combination have been in vogue in different centers from as early as 2004, as published by Frank et al from MD Anderson [7].…”
Section: Tumor Factorsmentioning
confidence: 99%